(untitled) (West African Journal on Sustainable Development, 2024)
Background: Infant feeding in the context of HIV has been a public health problem, especially in resource poor settings. Despite the ongoing fight against HIV/AIDS at the global, national and local levels, the impact of HIV/AIDS is usually pronounced among certain individuals, many of whom are the women living in the rural areas. This study was done to determine the effect of IEC on the infant feeding patterns of HIV- positive nursing mothers in rural communities of Anambra State, Nigeria. Methods: A quasi-experimental study was conducted among 310 HIV-positive nursing mothers from the rural communities in Anambra State, Nigeria using pre-tested, semi-structured interviewer administered questionnaires to obtain information from the respondents. The respondents were selected using two- stage sampling technique and were followed up for 3 months. Data were analyzed using SPSS version 22, and associations between dependent and independent variables were tested using Fisher’s exact test, Chi-square test and T-test as appropriate. Level of statistical significance was set at ≤ 5%. Results: At baseline, exclusive breast feeding in the first 6 months was preferred and practiced by 69.4% and 68.7% of the respondents in the intervention and control groups respectively, followed by mixed feeding (22.5% and 16.7% respectively). There was no difference in the preferred infant feeding options of the respondents in both groups. (p = 0.987). At the end of 3 months, majority of the respondents in both groups (72.0% and 73.9% respectively) still preferred and practiced exclusive breastfeeding, followed by mixed feeding (20.7% and 13.4% respectively), with no significant difference achieved (p = 0.103). Conclusion: This study has shown that IEC had no effect on the infant feeding patterns of the HIV-positive mothers in rural communities of Anambra State, Nigeria. Despite the fact that majority of the respondents preferred and practiced exclusive breastfeeding in the first 6 months post delivery, some respondents preferred and practiced mixed feeding in the first 6 months post delivery; which is a threat to the infants’ HIV free survival in Anambra State . There is a need for regular HIV and infant feeding counseling and education, targeted at HIV positive mothers in the rural settings of Anambra State.